Sleep quality among teachers of an educational institution during the COVID-19 health emergency, Peru, 2021 - Sisniegas-Vergara, César Edgardo (2023)
Objective: The COVID-19 pandemic affected the quality of life of the population worldwide. The countries took several protective measures to avoid contagion, including social isolation, teleworking and distance education. As schools closed, teachers took over primarily online teaching. The study main objective was to determine the sleep quality among teachers of a public educational institution in the district of Máncora, Peru, during the COVID-19 pandemic social isolation. Materials and methods: An observational, cross sectional and prospective study. The Pittsburgh Sleep Quality Index was used to assess 59 preschool, primary and secondary school teachers who taught through distance education from March to December 2021.Results: The average age was 44.3 ± 8.89 years. Women accounted for 64.4 %, specialist teachers—i.e., those who have expertise in a particular field—55.9 %, secondary school teachers 55.9 %, primary school teachers 30.5 % and preschool teachers 13.6 %. The affected sleep quality parameters were the following: 69.5 % had poor sleep quality, 67.8 % inadequate sleep latency, 61 % sleep duration of less than five hours, 27.1 % habitual sleep efficiency of less than 65 % and49.2 % sleep disturbances. Moreover, 50.8 % reported using a sleeping medication more than once a week and 39 % severe daytime dysfunction. There was an association between sleep quality and the components subjective sleep quality, sleep latency, sleep duration, habitual sleep efficiency and daytime dysfunction. Nonetheless, there was no association with sex, educational level and teaching specialty. Conclusions: Teachers of an educational institution in Máncora had a high prevalence of poor sleep quality and the most affected components were sleep latency, daytime dysfunction and sleep disturbances.